2012
DOI: 10.1021/jm300630p
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Diverse Human Dihydroorotate Dehydrogenase Inhibitors as Immunosuppressive Agents by Structure-Based Virtual Screening

Abstract: This study applied an efficient virtual screening strategy integrating molecular docking with MM-GBSA rescoring to identify diverse human dihydroorotate dehydrogenase (hDHODH) inhibitors. Eighteen compounds with IC(50) values ranging from 0.11 to 18.8 μM were identified as novel hDHODH inhibitors that exhibited overall species-selectivity over Plasmodium falciparum dihydroorotate dehydrogenase (pfDHODH). Compound 8, the most potent one, showed low micromolar inhibitory activity against hDHODH with an IC(50) va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 51 publications
1
58
0
Order By: Relevance
“…It is anchored at the inner mitochondrial membrane. 10 As an essential enzyme that catalyzes dihydroorotate to orotic acid, DHODH plays a critical role in the de novo pyrimidine biosynthesis of DNA and RNA. 11 Rapidly proliferating cells, such as cancer cells and lymphocytes, mainly depend on de novo pyrimidine biosynthesis to support their growth rate, indicating that this enzyme is a potential target in the treatment of cancer and autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is anchored at the inner mitochondrial membrane. 10 As an essential enzyme that catalyzes dihydroorotate to orotic acid, DHODH plays a critical role in the de novo pyrimidine biosynthesis of DNA and RNA. 11 Rapidly proliferating cells, such as cancer cells and lymphocytes, mainly depend on de novo pyrimidine biosynthesis to support their growth rate, indicating that this enzyme is a potential target in the treatment of cancer and autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…11 Rapidly proliferating cells, such as cancer cells and lymphocytes, mainly depend on de novo pyrimidine biosynthesis to support their growth rate, indicating that this enzyme is a potential target in the treatment of cancer and autoimmune diseases. 10 A previous study suggested that DHODH is required for rapid proliferation of tumor cells, playing an important role in tumorigenesis and tumor development. 12 Using a unique Homeobox A9-driven leukemia model, Sykes et al .…”
Section: Introductionmentioning
confidence: 99%
“…Because of these favorable hydrophobic interactions at subsite S1 ( Fig. The longer propyl group (12) could not be suitable for the small cavity any more but for the large hydrophobic cavity around Leu58, leading to an improved bioactivity compared to 11. However, due to the limited space around residue Met111, bulky hydrophobic moieties like ethyl would not be accommodated properly, thus compound 9 is about 5-fold less potent than compound 8 (355.7 nM vs. 66.2 nM).…”
Section: Binding Mode Analysismentioning
confidence: 99%
“…8 Taking into account the significance of pyrimidine for cellular proliferation and metabolism, blocking the pyrimidine de novo synthesis pathway by inhibiting hDHODH would be a promising treatment for cancer and immunological diseases, such as melanoma, multiple sclerosis and rheumatoid arthritis. [9][10][11][12][13][14] Leflunomide, a well-known inhibitor of hDHODH, was approved by the FDA for the treatment of rheumatoid arthritis more than 10 years ago. [9][10][11][12][13][14] Leflunomide, a well-known inhibitor of hDHODH, was approved by the FDA for the treatment of rheumatoid arthritis more than 10 years ago.…”
Section: Introductionmentioning
confidence: 99%
“…For example, AutoDock 4.0 was recently used to discover novel antiplasmodial compounds as potential cytochrome bc 1 inhibitor starting points for medicinal chemistry optimization [95]. Glide was efficiently used for screening a library of compounds and retrieve 18 molecules with IC 50 values ranging from 0.1 to 19 μM as hDHODH inhibitors while showing species selectivity [97]. Glide was efficiently used for screening a library of compounds and retrieve 18 molecules with IC 50 values ranging from 0.1 to 19 μM as hDHODH inhibitors while showing species selectivity [97].…”
Section: Examplesmentioning
confidence: 99%